2022
DOI: 10.1111/tbed.14566
|View full text |Cite
|
Sign up to set email alerts
|

Aichivirus C isolate is a diarrhoea‐causing pathogen in goats

Abstract: Aichivirus C is an emerging virus in goats, but its biological significance remains unknown. In this study, 18 diarrheic and 16 non‐diarrheic faecal samples of kids were collected from a farm with an on‐going diarrheic outbreak in Sichuan Province, China in May 2021. Of these samples, 77.8% (14/18) of diarrheic samples were detected as Aichivirus C positive by RT‐PCR, which was significantly higher than that of non‐diarrheic faces (0%, p < .001); meanwhile, other common diarrhoea‐causing pathogens in goats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Members of the genus Kobuvirus , genetically closely related to human AiVs, have been identified in Italy from a wide range of domestic and wild animals, suggesting a mutual exchange of viruses [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Kobuvirus , genetically closely related to human AiVs, have been identified in Italy from a wide range of domestic and wild animals, suggesting a mutual exchange of viruses [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…AiV was found in different animals in Europe: in Hungary in healthy piglets (Sus scrofa domestica) [Reuter et al 2009], in Italy in Mussels and Shellfish [Fusco et al 2017 and, in dogs [Kapoor et al 2011, Di Martino et al 2013, in cats [Di Martino et al 2015], pipistrelle bat [Diakoudi et al 2020], in domestic and wild ungulates [Di Martino et al 2021] and in goats [Abi et al 2022]. Some authors [Kapoor et al 2011) identified in domestic dogs (with gastroenteritis) a kobuvirus closely related to human aichivirus thus witnessing cross-species transmission in cohabiting species.…”
Section: Discussionmentioning
confidence: 99%
“…Aichiviruses (AiVs), belong to the Kobuvirus genus of the Picornaviridae family. Kobuviruses were associated with gastrointestinal diseases and fecal-oral infection, not only in humans, but also in dogs, cats, cattle and pigs [Abi et al 2022, Bergallo 2017, Diakoudi et al 2020, Kaikkonen 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The isolated strains were then purified via plaque technique when CPE was over 80% after three culture generations, during which virus titers were counted and expressed as the TCID 50 . The procedures followed for indirect immunofluorescence (IF) assay and transmission electron microscopy were as previously described ( 27 ). As a note, an anti-KoV polyclonal antibody was prepared in our laboratory for IF.…”
Section: Methodsmentioning
confidence: 99%